2014
DOI: 10.1080/03043797.2014.895707
|View full text |Cite
|
Sign up to set email alerts
|

Relationships, variety & synergy: the vital ingredients for scholarship in engineering education? A case study

Abstract: This paper begins with the argument that within modern-day society, engineering has shifted from being the scientific and technical mainstay of industrial, and more recently digital change to become the most vital driver of future advancement. In order to meet the inevitable challenges resulting from this role, the nature of engineering education is constantly evolving and as such engineering education has to change. The paper argues that what is needed is a fresh approach to engineering education -one that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Moreover, newly qualified graduates often feel 'incompetent' [4], and experience difficulty in transitioning into the workplace as graduate engineers [5] [6]. This is perhaps unsurprising, given that that there is little, if any, correlation between academic performance and success in the workplace [7]. It should, perhaps, be noted that the call for graduates who can 'hit the ground running' with appropriate skills is contested; indeed, previous studies suggest that education is about 'higher skills' which equips students to be leaders in their chosen professions [7] [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, newly qualified graduates often feel 'incompetent' [4], and experience difficulty in transitioning into the workplace as graduate engineers [5] [6]. This is perhaps unsurprising, given that that there is little, if any, correlation between academic performance and success in the workplace [7]. It should, perhaps, be noted that the call for graduates who can 'hit the ground running' with appropriate skills is contested; indeed, previous studies suggest that education is about 'higher skills' which equips students to be leaders in their chosen professions [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…This is perhaps unsurprising, given that that there is little, if any, correlation between academic performance and success in the workplace [7]. It should, perhaps, be noted that the call for graduates who can 'hit the ground running' with appropriate skills is contested; indeed, previous studies suggest that education is about 'higher skills' which equips students to be leaders in their chosen professions [7] [8]. On the other hand, there is some argument that the development of workplace skills is better done in the workplace [9].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different studies focused on issues faced in higher education, one of the studies proposed by Clark [7] who identified an equation to represent the key elements in higher education teaching which, can contribute towards the improvement in the student's performance. The relationship was described as follows [7,8]:…”
Section: Introductionmentioning
confidence: 99%